Some Results on Fractional m-Point Boundary Value Problems - Huijuan Zhu; Baozhi Han; Jun Shen (Journal of Function Spaces)
In this paper, we will apply some fixed-point theorems to discuss the existence of solutions for fractional m-point boundary value problems D0+qu″t=htfut,t∈0,1,1<q≤2,u′0=u″0=u1=0,u″1−∑i=1m−2αiu‴ξi=0. In addition, we also present Lyapunov’s inequality and Ulam-Hyers stability results for the given m-point boundary value problems.